2010
DOI: 10.1016/j.tra.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Unintended environmental impacts of nighttime freight logistics activities

Abstract: In recent years, the reduction of freight vehicle trips during peak hours has been a common policy goal. To this end, policies have been implemented to shift logistics operations to nighttime hours. The purpose of such policies has generally been to mitigate congestion and environmental impacts. However, the atmospheric boundary layer is generally more stable during the night than the day. Consequently, shifting logistics operations to the night may increase 24-hour average concentrations of diesel exhaust pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The higher overnight near-road traffic-related PM2.5 is consistent with previous literature based on field [30] and modeling studies [8]. Previous research suggested that this trend may be due to the more stable/restrictive atmospheric boundary layer conditions during the night [42].…”
Section: Traffic-related Pm25 Concentrations From Highways and Artersupporting
confidence: 90%
“…The higher overnight near-road traffic-related PM2.5 is consistent with previous literature based on field [30] and modeling studies [8]. Previous research suggested that this trend may be due to the more stable/restrictive atmospheric boundary layer conditions during the night [42].…”
Section: Traffic-related Pm25 Concentrations From Highways and Artersupporting
confidence: 90%
“…Delivery times can be regulated to off peak time to decrease CO 2 -emissions. Night-time deliveries might reduce traffic congestion and emissions (Browne, Allen, Anderson, & Woodburn, 2006), however Sathaye et al showed that night-time deliveries could have the opposite effect due to the atmospheric layer (Sathaye, Harley, & Madanat, 2010). Traffic can also be restricted in terms of property rights, for instance by licensing ownership as in Singapore.…”
Section: Environmental Zones Restrictions Of Vehicle Circulation Andmentioning
confidence: 99%
“…This phenomenon may be due to the large differences in the background and model of G&SL development in different countries [35]. Moreover, the knowledge gap caused by the wide extension of G&SL and the scattered knowledge structure make the research still focus on the respective fields of researchers, such as sustainable development [36], environment governance [37] and transportation planning [38]. Therefore, at present, the cooperation between academic institutions of different backgrounds has not been widely carried out.…”
Section: Countries/organizations Collaboration Analysismentioning
confidence: 99%